Study on understanding and perception among ACIS students of UiTM Puncak Alam towards ASNB investments / Siti Nurzakiah Mohd Salihin - Mohd Salihin, Siti Nurzakiah (2019)
ASNB is one of the investments that under the unit trust fund investment that established in 1979. It’s a wholly-owned subsidiary of Permodalan Naional Berhad (PNB). This fund is only eligible to Malaysian Bumiputera. The fund objective is to generate long-term, consistent and competitive returns to the Unitholders whilst ensuring the preservation of capital at minimal risk tolerance level. ASNB has two types of funds under its management – fixed price funds and variable price funds. At this moment, ASNB consists 14unit trust funds such as ASB, ASB2 and ASN.Amanah Saham Bumiputera (ASB) fund was launched on the 2nd of January 1990. This fund is only eligible to Malaysian Bumiputera. ASB is an income equity fund with a fixed price per unit at RM1.00. It is also a capital guarantee fund. The maximum investment for each adult eligible individual is limited to RM200,000. Since launched in 1990, ASB is one of the best performing funds under PNB management.